III‐nitride microcrystal cavities with quasi whispering gallery modes grown by molecular beam epitaxy. Issue 5 (29th January 2016) - Shubina, T. V.; Jmerik, V. N.; Davydov, V. Yu.; Kazanov, D. R.; Smirnov, A. N.; Nechaev, D. V.; Kuznetsova, N.; Pozina, G.; Hemmingsson, C.; Ivanov, S. V.
Abstract: This paper analyzes current trends in fabrication of III‐nitride microresonators exploiting whispering gallery modes. Novel cup‐cavities are proposed and their fabrication from GaN and InN by molecular beam epitaxy on patterned substrates is described. These cup‐cavities can concentrate the mode energy in a subwavelength volume. Their mode energies are stable up to room temperature, being identical in large microcrystals. In these cavities, mode switching can be realized by means of refractive index variation. Cup‐cavity modes, being inferior to plasmonic resonances in the respect of integral emission enhancement, have advantages for spectrally selective amplification of quantum transitions in site‐controlled nano‐emitters. Imaging (left) and high‐spatial‐resolution photoluminescence spectra (right) of an InN cup‐cavity. Abstract : Optical cavities with whispering gallery modes play an important role in nanophotonics. They can enhance the recombination rate of nano‐emitters by the Purcell effect and boost the light extraction efficiency. This paper reviews such state‐of‐the‐art microresonators made from III‐nitride semiconductors and introduces a new cavity type ‐ cup‐cavity fabricated solely by molecular beam epitaxy.